2013
DOI: 10.1007/978-1-62703-453-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Circulating MicroRNAs in Exosomes/Extracellular Vesicles from Serum or Plasma by qRT-PCR

Abstract: Small extracellular vesicles are released from both healthy and disease cells to facilitate cellular communication. They have a wide variety of names including exosomes, microvesicles and microparticles. Depending on their size, very small extracellular vesicles originating from the endocytic pathway have been called exosomes and in some cases nanovesicles. Collectively, extracellular vesicles are important mediators of a wide variety of functions including immune cell development and homeostasis. Encapsulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 21 publications
(26 reference statements)
1
67
0
Order By: Relevance
“…The cargo can include genetic material such as mRNA, microRNA (miRNA), or even small amounts of DNA (Moldovan et al 2013), and proteins including transcription factors, cytokines, and growth factors, have also been described. Importantly, MVs also carry cellular receptors and transmembrane proteins on their surface characteristic of the cells from which they were released.…”
Section: Introductionmentioning
confidence: 99%
“…The cargo can include genetic material such as mRNA, microRNA (miRNA), or even small amounts of DNA (Moldovan et al 2013), and proteins including transcription factors, cytokines, and growth factors, have also been described. Importantly, MVs also carry cellular receptors and transmembrane proteins on their surface characteristic of the cells from which they were released.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are small, non-coding RNAs that have the ability to regulate whole networks of genes through transcriptional and translational regulation. In the circulation they are commonly found enclosed in extracellular vesicles (EVs) [7], bound to lipoproteins [8], or complexed with Argonaute-2 [9]. Furthermore, in vitro studies have shown that numerous cell types are capable of releasing miRNA in these complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of heparinase significantly increases the cost of RNA measurement. Recent studies also suggest that citrate treated plasma shows lower miRNA concentrations based on qPCR measurement compared to EDTA treated plasma from the same individual [56, 96]. …”
Section: Factors Affect the Spectrum Of Extracellular Rnamentioning
confidence: 99%